Passivity-Based Stability Analysis of Hydraulic Equilibria in 4th Generation District Heating Networks. Issue 19 (2021) - Strehle, Felix; Vieth, Jonathan; Pfeifer, Martin; Hohmann, Sören
Abstract: In this paper, we analyze the stability of hydraulic, i.e. pressure and flow, equilibria in 4th generation district heating networks (DHNs). We consider the hydraulic behavior of a general class of DHNs with an arbitrary number of distributed heat generation units (DGUs) and end-users connected through a network of pipes. For each subsystem, we first derive a model in form of an explicit port-Hamiltonian system with nonlinear resistive structure. Based on these models and with methods from equilibrium-independent passivity (EIP), we prove the stability of the DHN's hydraulic equilibria. From our results, we deduce requirements for a plug-and-play control of DHNs and draw conclusions for future work.